Caffeine and adenosine A 2A receptor inactivation decrease striatal neuropathology in a lentiviral-based model of Machado–Joseph disease - Gonçalves, Nélio (2013)
Objective: Machado–Joseph disease (MJD) is a neurodegenerative disorder associated with an abnormal CAG expansion, which translates into an expanded polyglutamine tract within ataxin-3. There is no therapy to prevent or modify disease progression. Because caffeine (a nonselective adenosine receptor antagonist) and selective adenosine A2A receptor (A2A R) blockade alleviate neurodegeneration in different brain diseases, namely at early stages of another polyglutamine-related disorder such as Huntington’s disease, we now tested their ability to control MJD-associated neurodegeneration. Methods: MJD was modeled by transducing the striatum of male adult C57Bl/6 mice with lentiviral vectors encoding mutant ataxin-3 in one hemisphere and wild-type ataxin-3 in the other hemisphere (as internal control). Caffeine (1g/L) was applied through the drinking water. Mice were killed at different time points (from 2 to 12 weeks) to probe for the appearance of different morphological changes using immunohistochemical analysis. Results: Mutant ataxin-3 caused an evolving neuronal dysfunction (loss of DARPP-32 staining) leading to neurodegeneration (cresyl violet and neuronal nuclei staining) associated with increased number of mutant ataxin-3 inclusions in the basal ganglia. Notably, mutant ataxin-3 triggered early synaptotoxicity (decreased synaptophysin and microtubule-associated protein-2 staining) and reactive gliosis (glial fibrillary acidic protein and CD11b staining), which predated neuronal dysfunction and damage. Caffeine reduced the appearance of all these morphological modifications, which were also abrogated in mice with a global A2A R inactivation (knockout). Interpretation: Our findings provide a demonstration that synaptotoxicity and gliosis are precocious events in MJD and that caffeine and A2A R inactivation decrease MJD-associated striatal pathology, which paves the way to consider A2A Rs as novel therapeutic targets to manage MJD.